The New Regionalism. Policy Implications for Rural Regions - Ortiz-Guerrero, César E. (2013)
The New Regionalism – NR, is an arena in which diverse movements, theoretical approaches and policies converge, and is increasingly accepted and used in the field of regional planning. As a macro-structure, the NR articulates different movements and streams of thought, with regional development as the common goal, although primarily focused on metropolitan regions. This paper analyzes the NR, outlines the current contents and theoretical underpinnings identifies the main criticisms and lessons learned with potential application in rural regions. It also suggests adjustments and a policy framework that can be applied within the context of rural territories.